2000
DOI: 10.1080/15298660008984534
|View full text |Cite
|
Sign up to set email alerts
|

Benzene and Total Hydrocarbon Exposures in the Upstream Petroleum Oil and Gas Industry

Abstract: Occupational exposures to benzene and total hydrocarbons (THC) in the Canadian upstream petroleum industry are described in this article. A total of 1547 air samples taken by 5 oil companies in various sectors (i.e., conventional oil/gas, conventional gas, heavy oil processing, drilling and pipelines) were evaluated and summarized. The data includes personal long- and short-term samples and area long-term samples. The percentage of samples over the occupational exposure limit (OEL) of 3.2 mg/m3 or one part per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Recent studies report a benzene exposure averaged over a full shift well below 0.1 ppm during ordinary activity, ranging from below 0.001 to 0.69 ppm [19,29]. Low full shift exposures for most job categories are also reported internationally from the upstream petroleum industry [20,[30][31][32]. However, specific tasks causing high short-term exposures, such as cleaning of tanks containing residues of crude oil with a reported maximum of Rate ratios are stratified on the year of the first engagement in the offshore-related petroleum industry (''first exposure'') and adjusted for gender, age at inclusion into the cohort, year of first exposure, and education using the Cox proportional hazard regression model.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies report a benzene exposure averaged over a full shift well below 0.1 ppm during ordinary activity, ranging from below 0.001 to 0.69 ppm [19,29]. Low full shift exposures for most job categories are also reported internationally from the upstream petroleum industry [20,[30][31][32]. However, specific tasks causing high short-term exposures, such as cleaning of tanks containing residues of crude oil with a reported maximum of Rate ratios are stratified on the year of the first engagement in the offshore-related petroleum industry (''first exposure'') and adjusted for gender, age at inclusion into the cohort, year of first exposure, and education using the Cox proportional hazard regression model.…”
Section: Discussionmentioning
confidence: 97%
“…While benzene (Group 1) (IARC 1987) and ethylbenzene (Group 2b) (IARC 2000) have been classified as carcinogens, the main concern for exposures to toluene and xylene are their effects on the central nervous system. Studies performed in the upstream petroleum industry have reported wide ranges of volatile organic hydrocarbon concentrations measured in air (Verma et al 2000;Glass et al 2000;SteinsvĂ„g et al 2007;BrĂ„tveit et al 2007;Runion 1988;Kirkeleit et al 2006a), as well as increased risk of cancer types that has been associated with these hydrocarbons such as leukemia (Glass et al 2003;Kirkeleit et al 2008;Aas et al 2009), multiple myeloma (Kirkeleit et al 2008), malignant melanoma (Lewis et al 2000;Sorahan et al 2002;Gun et al 2004Gun et al , 2006Christie et al 1991;Wong and Raabe 2000), and kidney cancer (Gun et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…No published studies are available of the health of workers involved specifically in the recent upsurge of shale and oil drilling using hydraulic fracturing. Verma et al (2000) summarized data from over 1500 shortand long-term personal and area air samples for benzene and total petroleum hydrocarbons in the Canadian upstream oil and gas industry. Exposures were characterized by task, job description, and industry sector when possible.…”
Section: Occupational Exposures Associated With Upstream Oil and Gas mentioning
confidence: 99%